Frontispiece: The Electronic Structure of the Al3− Anion: Is it Aromatic?. Issue 27 (26th June 2015) - Mercero, Jose M.; Matito, Eduard; Ruipérez, Fernando; Infante, Ivan; Lopez, Xabier; Ugalde, Jesus M.
<x xml:space="preserve">Abstract</x> Aromaticity Study The lowest lying singlet, triplet, and quintet spin states of D3h Al3 have strong multireference character, which impedes the straightforward application of the Hückel–Baird‐like electron counting rules based on the inspection of the molecular orbitals. However, electron delocalization can be assessed by inspection of the electron delocalization indices and induced ring currents evaluated from their corresponding multiconfigurational wavefunctions. The calculations suggest that the singlet and triplet states do have large electron delocalization, while the quintet has much less. For more details see the Communication by J. M. Mercero et al. on page 9610 ff.